2006
DOI: 10.2495/air06059
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative relationship between visibility and mass concentration of PM2.5 in Beijing

Abstract: The pollution of PM2.5 is a serious environmental problem in Beijing. The annual average concentration of PM2.5 in 2001 from seasonal monitor results was more than six times that of the US national ambient air quality standards proposed by US EPA. The major contributors to mass of PM2.5 were organics, crustal elements and sulfate. The chemical composition of PM2.5 varied largely with season, but was similar at different monitor stations in the same season. The fine particles (PM2.5) cause atmospheric visibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 2 publications
3
40
0
Order By: Relevance
“…This means that PLAM/h has significant capability in describing optimal or inferior visibility and, moreover, its seasonal difference is great. This finding is consistent with the climate observation result that the aerosol concentration high value in summer appears at the same rate as with low visibility (Wang and Liu, 2006).…”
Section: Analysis Of Seasonal Characteristics Of Plam/h Index and Vissupporting
confidence: 82%
“…This means that PLAM/h has significant capability in describing optimal or inferior visibility and, moreover, its seasonal difference is great. This finding is consistent with the climate observation result that the aerosol concentration high value in summer appears at the same rate as with low visibility (Wang and Liu, 2006).…”
Section: Analysis Of Seasonal Characteristics Of Plam/h Index and Vissupporting
confidence: 82%
“…Thus, with an increase in relative humidity, the correlation between the visibility and the concentration of PM 2.5 becomes weaker. A similar situation was found for the summer in Beijing (Wang and Liu, 2006).…”
Section: Correlation Between Visibility and The Concentration Of Pm 2supporting
confidence: 82%
“…The results show that the concentration of fine particles also plays an important role in reducing visibility in Hangzhou. This phenomenon has also been observed in Beijing (Song et al, 2003;Wang and Liu, 2006), Guangzhou (Tan et al, 2009b), Shanghai (Fu et al, 2008) and Jinan (Yang et al, 2007), Seoul (Kang et al, 2004) and the mid-Atlantic region (Chen et al, 2003). …”
Section: Influence Of Fine Particulate Matter On Visibilitymentioning
confidence: 55%
“…The high concentration of PM 2.5 could have significant adverse impacts on the atmospheric visibility and the human health. For example, previous studies indicated that the PM 2.5 was the main cause of reduced visibility in Beijing (Wang et al, 2006;Zhou et al, 2012a). Such fine particles can also result in serious human health problems (e.g., cardiovascular diseases, respiratory irritation, and pulmonary dysfunction) since they contain microscopic solids or liquid droplets which are toxic and can get deep into the human body (Cao et al, 2012;Haberzettl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%